Minutes of the 47th Meeting of BRAC University Academic Council (AC) - Academic Council, BRAC University (Vice Chancellor's Office, BRAC University, 2013)
1. Confirmation of Minutes of the 46th Meeting of the Academic Council. 2. Review of the progress and implementation of decisions of the 46th Meeting of the Academic Council. 3. Approval of the results at the end of Spring 2012. 4. Proposal for Equivalence of some Microbiology and Biotechnology courses. 5. Proposal for Double Major and Minor options in Microbiology and Biotechnology. 6. Proposal for Certificate Course in Broadcast and Cross Media Journalism with Pathshala. 7. Proposal for Customized EMBA Program. 8. Proposed BDI Advisory Group. 9. Update on Admission Test. 10. Update on 8th Convocation. 11. Miscellaneous: 11.1 Credit Exemption Policy for English Language Course. 11.2 Continuation of Studies. 11.3 Appeal for Additional Time for Continuation of Study. 11.4 Rules of Business for Institutes. 11.5 Rules of Signing of Contracts.